Morphological Characterization of Baladi Goats in the West Bank, Palestine - Jihad M. Abdallah; Jamal Abo Omar (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
A field survey was conducted to characterize local “Baladi” goats in the West Bank, Palestine. A total of 104 flocks were sampled in the Southern, Central and Northern geographical regions. Qualitative and quantitative characteristics were recorded on 104 bucks and 416 does. Significant differences were found between males and females and among regions. The multivariate discriminant analyses were able to identify seven body measures for bucks and eight body measures for does which were significant in discriminating Baladi goat populations from the three regions. For bucks, the squared Mahalanobis distances showed higher differentiation between the Southern and Central regions (11.83) and between the Southern and Northern regions (8.02) than between the Central and Northern regions (4.27). For does, distances were similar (3.05, 2.90, and 3.13 between Southern and Central, between Southern and Northern, and between Central and Northern regions, respectively). Canonical discriminant analyses showed that 81.6% of bucks and 74.1% of does were correctly classified into their geographic areas with highest rates found in the Southern region (96.9% of bucks and 88.3% of does). These results form the basis for the development of future characterization and conservation plans of Baladi goats in Palestine.